O simbolismo do azul em Ernesto Penafort - Ferreira, Cleiciane Maia (2014)
This dissertation aims to, based of comparative literature and interdisciplinary character that itself requires, make the study of symbolism of the blue recurring in the poetry of Ernesto Penafort. It begins with reflections on the evolution of theories about the colors in the visual arts treading the paths to aesthetic analysis of the blue to modern artists and the poet. Then, the study focused on discussions about the lyrical subject, the philosophical stance of the poet and aesthetic applications based on hermeneutics and blue iconology. Gradually, the research centered on the aesthetic questions about the subjectivity and its consequences in discussions with poems of love and anguish. Finally, the last part of this study apresent the Poethic Antology of Ernesto Penafort as concrete product of the objective of this research. Keywords: poetry, lyrical, colors, hermeneutics, iconology.